Tik Tok Users' Opinions About Da’wah Religious ModerationIn Tik Tok Conversation - Rakatiwi, Yolanda; Halwati, Umi; Nawawi, Nawawi (Jurnal Dakwah dan Komunikasi, 2023)
This research was conducted to describe the views of influential people in Tk Tok conversations around religious moderation. The ideas and subjects expressed by Mega influencers, Macro influencers, and Nano influencers are examined in this research using public opinion, the agenda-forming model, and the spiral of silence. This research methodology uses qualitative descriptive content analysis techniques. The keyword "religious moderation" in Vivo was used to search for research data. The majority of research findings are positive public perceptions of Tik Tok influencers. Five accounts on the nano-influencer account criticized religious moderation, while two accounts were neutral. The research results show that the majority of TikTok influencers' views on the subject of religious moderation are favorable. There are several influencer views including neutral, negative or positive opinions. Most of the public opinions from influencers on TikTok are positive. On the @basyasman00 account there are several negative comments, and 1 account has a neutral tone regarding religious moderation. The mass media agenda and the agenda of influencers on social media shape public opinion.